Faktor-Faktor yang Berhubungan dengan Kunjungan Antenatal Care (K4) pada Ibu Hamil di Wilayah Kerja Puskesmas Tarus Kupang - Senci Marselin Beti; Muntasir, Muntasir; Masrida Sinaga (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
The Maternal Mortality Rate (MMR) is an important measure of a country's health sector progress. Governments aim to lower MMR through initiatives like safe motherhood programs, which include antenatal care (ANC) services. ANC consists of regular pregnancy check-ups to prevent maternal fatalities, with six visits being the minimum recommended number. Although Tarus Community Health Center has reached the K4 service goal, it has not yet met the necessary standards.Based on the data from the Tarus Community Health Center PWS report over the past three years, the National Health Sector SPM target of 100% has not been met. The average K4 coverage was 73.10% in 2020, 70.48% in 2021, and 74.9% in 2022. The underutilization of ANC services by pregnant women at Tarus Health Center is the primary factor contributing to this low performance.This research aims to identify factors related to ANC visits in pregnant women at Tarus Community Health Center in Kupang Regency. The study utilized a quantitative descriptive research method with an analytical survey and cross-sectional approach, analyzing data from 43 individuals using the chi-square test. The findings suggest a correlation between maternal knowledge (p=0.030), parity (p=0.014), culture (p=0.000), and accessibility (p=0.014) with ANC visits. However, the study did not find a significant relationship between mother's attitude (p=0.551) and ANC visits in the research area.The community health center should improve maternal and child health education through electronic and print media. Regular visits and counseling for pregnant women can motivate them to attend antenatal care appointments.